1976
DOI: 10.1021/jm00225a010
|View full text |Cite
|
Sign up to set email alerts
|

Etodolic acid and related compounds. Chemistry and antiinflammatory actions of some potent di- and trisubstituted 1,3,4,9-tetrahydropyrano[3,4-b]indole-1-acetic acids

Abstract: A series of 37 1-ethyl- and 1-n-propyl-1, 3, 4, 9-tetrahydropyrano[3, 4-b]indole-1-acetic acids bearing one, or two, substituents on the benzene ring has been synthesized via the acid-catalyzed condensation of a substituted tryptophol with ethyl propionylacetate or ethyl butyrylacetate. Antiinflammatory and ulcerogenic effects were examined and the results show that 1, 8-diethyl-1, 3, 4, 9-tetrahydropyrano[3, 4-b]indole-1-acetic acid (etodolic acid, USAN) is a potent agent, particularly active against a chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…The analgesic drug pemedolac [122][123][124] , analogues of etodolac 125,126 and the synthesis of the alkaloids hobartine and aristoteline 127 were initiated by the C-3 alkylation of isatins to yield dioxindoles that were then reduced to the corresponding indoles by the use of lithium aluminum hydride (Schemes 36 and 37). In a similar manner, 1-acylisatins can be reduced to 1-alkylindoles by BH 3 .THF in high yields 99 (Scheme 38).…”
Section: Scheme 35mentioning
confidence: 99%
“…The analgesic drug pemedolac [122][123][124] , analogues of etodolac 125,126 and the synthesis of the alkaloids hobartine and aristoteline 127 were initiated by the C-3 alkylation of isatins to yield dioxindoles that were then reduced to the corresponding indoles by the use of lithium aluminum hydride (Schemes 36 and 37). In a similar manner, 1-acylisatins can be reduced to 1-alkylindoles by BH 3 .THF in high yields 99 (Scheme 38).…”
Section: Scheme 35mentioning
confidence: 99%
“…Etodolac ( fig. 1) is a nonsteroidal anti-inflammatory drug (NSAID) of the pyranocarboxylic acid class (Humber 1992) developed in the 1970s (Demerson et al 1976). Early studies indicated that etodolac was an effective NSAID, with a favourable ratio of anti-inflammatory activity to adverse effects.…”
mentioning
confidence: 99%
“…The required isatins were prepared from anilines 4 and £ by cyclization of intermediate isonitrosoacetanilides (10,11). The remaining two were synthesized by oxidation of the appropriate substituted isatin derivatives (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%